Os pés dos que anunciam "boas novas" : análise comparativa das estratégias missionárias de capuchinhos e jesuitas no Congo e em Angola, de 1640 a 1669 - Mikaela Monteiro Moraes (2022)
This study consists of an analysis between the missionary strategies of two prominent religious orders in the 17th century - the Capuchins and the Jesuits. Both segments, coming from Catholicism, emerged in the 16th century as responses by their founders to the religious, political and social context in which they lived; because of that same reason they acquired a missionary and expansionist character, going beyond the borders of Europe. In particular, the work talk abort the activity of these priests in Congo and Angola, territories in central-west Africa, in the period from 1640 to 1669, corresponding to the rupture of the papal seat with the Portuguese crown. The action of the Capuchins among the native inhabitants of these regions was possible because of the weakening of the requisitions of the royal patronage with respect to the monopoly of navigation, trade and missions to peoples overseas. The Jesuits, having been aligned with the Portuguese purposes of conquest, ministered their teachings to owners and slaves in the great centralities, sharing the jealous feeling of the Portuguese conquerors. In the midst of these disputes were the contingencies, expectations and resistance of the societies that inhabited Congo and Angola. From correspondences, chronicles and reports, I analyze the tactics of both Catholic Orders to convey the Gospel in a context guided by political conquest, governed by the demands of mercantilism, and permeated by modern slavery.